Evaluating fertility and growth rate potential of indigenous sheep breeds submitted to heat stress under different management systems - Khan, Shakirullah; Khan, Imdad Ullah; Khan, Alam Zeb; Zaman, Shahid; Majid, Abdul; Rehman, Atiq Ur; Khan, Mumtaz Ali; Maris, Hamza; Ullah, Rahman; Qureshi, Subhan (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Sheep farming is an important source of livelihood in the southern Khyber Pakhtun Khwa province of Pakistan where they are reared under extensive system (ES). This system has limitations of improper feeding, rearing, and management which negatively affect their productivity. The present study compares different rearing systems and their stresses on fertility, behavior, and growth rate potential of two sheep breeds of Pakistan. Materials and Methods: Eighty ewes were selected; forty each from Damani and Balkhi breeds reared in semi-intensive system (SIS) and ES at Paharpur district, Dera Ismail Khan. Blood samples were collected in triplicate on days 0, 14, and 28 of May, and the molecular and behavioral stress, growth, and fertility rates were recorded. Results: The highest growth and fertility rate were observed in both the breeds in SIS than in ES (p < 0.01). The values of stress indicators (cortisol, heat shock protein (HSP-70)) and behavioral stress parameters were found lower in Damani breed as compared to Balkhi breed in both rearing systems (p < 0.01). All the molecular stress and behavioral stress parameters were negatively associated with metabolic hormones (T3 and T4) (p < 0.01). A positive correlation was observed among all the molecular stress and behavioral stress parameters (p < 0.01). Similarly, T3 and T4 were positively interlinked to one another (p < 0.01). Conclusion: It was concluded that both Damani and Balkhi sheep showed lower stress levels and better fertility and growth parameter in SIS than ES system of rearing. Local Damani breed exhibited well tolerant ability and genetic adaptation to the local environment as compared to Balkhi breed. J. Adv. Vet. Anim. Res., 7(1): 170-176, March 2020